Atherosclerotic Parameter Level Differences in Mongolian People Compared to Japanese People: A Brief Review of the Literature - Shuumarjav, Uurtuya (Central Asian Journal of Medical Sciences, 2018)
Objectives: In Mongolia, non-communicable disease caused morbidity and mortality related to lifestyle and metabolic diseases are increasing year after year. This review discusses the results of comparative studies related to lifestyle risk factors and the atherosclerotic parameters body mass index, glucose, insulin, and lipid level of Mongolian and Japanese people, as these are the known factors involved in metabolic and cardiovascular diseases. Methods: Academic literature was searched using electronic academic databases and handsearching reference lists for articles published in English and Mongolian on the topic. Results: The studies revealed that in comparison to Japanese subjects, a higher percentage of Mongolians smoked, and Mongolians had higher body mass index, heart rate, blood pressure, and insulin even though levels of serum total cholesterol and glucose were not different. Conclusion: The studies suggest that Mongolian people have higher risk of metabolic syndrome, which is a known main cause of CVDs, compared to Japanese people. On the other hand, climate, genetic and lifestyle differences might also increase non-communicable diseases in the Mongolian people.